Dramsko delo Daneta Zajca - Borovnik, Silvija (Jezik in slovstvo, 2003)
The article is the surway of plays written by Dane Zajc, who has become part of Slovene literary history not only as an excellent poet, but also as a playwright. His dramatic pieces, refered to rather modestly by the author as "the plays", complement and reflect his poetic world, maked by alienation and concieved with an idea that humans are solitary figures burdened by past or semi-past history. In Zajc's dramatic work poetry signifies a self-evident and expressive artistic part, through which also the mythical, dream-like and other parallel realities step into the dramatic space and time, with which the author indicates the cracks of time, even more so in the historical memory, which should not fade in the face of totalitarisms of the modern world.
Keywords: Zajc, Dane, 1929-; Slovene literature; slovenska književnost; slovenska dramatika; literarne študije